The interleukin-10 gene promoter polymorphism -1087AG does not correlate with clinical outcome in non-Hodgkin's lymphoma. - Kube, D.; Hua, T. D.; Kloss, M.; Kulle, B.; Brockmoller, J.; Wojnowski, L.; Loffler, M.; Pfreundschuh, M.; Trumper, L. (Genes Immun, 2007)
The Interleukin 10 (IL-10) gene is highly polymorphic, and the IL-10(-1087AG) (rs1800896) gene variation is the only so far studied intensively in association with certain diseases. Conflicting data have been published about an association of IL-10(-1087AG) gene variation with lower rates of complete remission and lower overall survival (OS) in patients with diffuse large B-cell lymphoma. To further investigate this in malignant lymphoma, we established the IL-10 genotypes in patients from the NHL-B1/ B2 studies from the German High-Grade Non-Hodgkin's Lymphoma Study Group. In our study, allele frequencies of lymphoma patients are comparable as in healthy controls. No increase of IL-10(-1087G) alleles was found. In addition we did not find any difference in OS or event-free survival between patients with IL-10(-1087AA) and the other genotypes. Comparable results were obtained for the IL-10 loci at -3538 (A/T), -1354 (A/G), -824 (C/T) and -597 (A/C) (rs1800890, rs1800893, rs1800871 and rs1800872).
Keywords: Gene Frequency; Germany; Humans; Interleukin-10/*genetics; Lymphoma, Large B-Cell, Diffuse/*genetics; *Polymorphism, Genetic; Promoter Regions, Genetic/*genetics; Remission, Spontaneous; Survival Analysis